Analysis of the Influence of Servant Leadership Style, Interpersonal Communication, and Work Motivation on the Organizational Commitment of Employees of Sukodono District - alamsyah, ashaby; Fauzi, Akhmad (East Asian Journal of Multidisciplinary Research, 2024)
The Sukodono District Office is an agency organization engaged in government institutions, the Sukodono District Office has a role in community services and village development in the Sukodono District area. The Sukodono District Office has employees consisting of several parts of the work field. This study aims to determine the influence of servant leadership style, interpersonal communication, and work motivation on the organizational commitment of employees in Sukodono District. This research focuses on Sukodono District employees. The population in the study is employees who work at the Sukodono District Office. The sample was obtained through the saturated sample technique by obtaining 41 respondents. The data analysis technique used in this study is Partial Least Square (PLS), with validity tests, reliability tests, and hypothesis tests. The results of the study show that Servant Leadership Style has a positive effect on Organizational Commitment, Interpersonal Communication has a positive effect on Organizational Commitment, and Work Motivation has a positive effect on Organizational Commitment.